Validation of Finite Volume Method by hot extrusion analysis of aluminium alloy - Bressan J.D.* (2019)
© 2018 Elsevier Ltd.Comparisons of FVM and Forge 2008 codes presented in ICEB 2015 suggested that solid metal extrusion can be modelled by FVM. Present work aim to validate FVM by comparisons with experimental results from grid stripe pattern technique of EN AW 6060 direct hot extrusion. Tests were conducted in controlled conditions: 400 oC and ram peed 2 and 5 mm/s. Grid displacements where measured and axial velocity fields were calculated and compared with good agreement with FVM numerical results. Simulations revealed a dead metal zone similar to experimental observation and a critical point of maximum sliding velocity near die entrance corner.